Prove that the following sequence is convergent: `u_1=sqrt(2),` `u_2=sqrt(2+sqrt(2)), ldots, u_n=sqrt(2+sqrt(2+sqrt(2+sqrt(2+cdots+sqrt(2+sqrt(2))))))`  

Expert Answers

An illustration of the letter 'A' in a speech bubbles

In order to prove that your sequence is convergent we will use the following theorem:

A sequence of real numbers is convergent if it is monotone and bounded.

1. proof of monotonicity

We will prove this by induction:

i) `x_2=sqrt(2+sqrt(2))>sqrt(2)=x_1` which proves the base.

ii) Assume that for every `k leq n`     `x_k>x_(k-1).`

iii) Now we use assumption for `k=n` and add number 2 to each side.

`2+x_n>2+x_(n-1)` hence

`x_(n+1)=sqrt(2+x_n)>sqrt(2+x_(n-1))=x_n` which proves inductive step.

2. proof that sequence is bounded

Since sequence is increasing we only need to find upper bound (lower bound is `x_1` ). We will prove that the upper bound is 2. Again we do this by induction:

i) `x_1=sqrt(2)<2`

ii)Assume that `x_n<2.`

iii) `x_(n+1)=sqrt(2+x_n)<sqrt(2+2)=2` which proves step of induction.

We have now proven that the sequence is convergent. 

We can also find the limit of the sequence:

We know that sequence is convergent meaning it has limit `a.` This means:

`lim_(n rightarrow infty) x_n=lim_(n rightarrow infty) sqrt(2+x_(n-1))`

`a=sqrt(2+a)`                                                       (1)

by squaring this equation we get

`a^2-a-2=0` solutions to this equation are `a_1=2` and `a_2=-1.` Since only `a_1=2` satisfies (1) that is our limit.


` `


See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial Team